"An Entry-Level Field:" A California Case Study on New Media in Youth Services Programming. Issue 1 (2nd January 2017) - Martens, Marianne
ABSTRACT: This article presents findings from a case study evaluation of a library in Southern California, which received LSTA Funding to incorporate iPads and new media into its youth services programming. While an abundance of new media is available for young children, much remains to be known about children, screens, and new media formats. Youth services librarians, too, are in a challenging position, as there are virtually no guidelines or best practices to follow in terms of implementing such new formats into programming. As a result, on-going professional development is needed.